Socioeconomic and demographic determinants of radiation treatment and outcomes in glioblastoma patients - Hsu, Eric J.; Thomas, Jamie; Timmerman, Robert D.; Wardak, Zabi; Dan, Tu D.; Patel, Toral R.; Sanford, Nina N.; Vo, Dat T. (Frontiers in Neurology, 2022)
Introduction: Poor outcomes in glioblastoma patients, despite advancing treatment paradigms, indicate a need to determine non-physiologic prognostic indicators of patient outcome. The impact of specific socioeconomic and demographic patient factors on outcomes is unclear. We sought to identify socioeconomic and demographic patient characteristics associated with patient survival and tumor progression, and to characterize treatment options and healthcare utilization. Methods: A cohort of 169 patients with pathologically confirmed glioblastomas treated at our institution was retrospectively reviewed. Multivariable cox proportional hazards analysis for overall survival (OS) and cumulative incidence of progression was performed. Differences in treatment regimen, patient characteristics, and neuro-oncology office use between different age and depressive disorder history patient subgroups were calculated two-sample t-tests, Fisher’s exact tests, or linear regression analysis. Results: The median age of all patients at the time of initiation of radiation therapy was 60.5 years. The median OS of the cohort was 13.1 months. Multivariable analysis identified age (Hazard Ratio 1.02, 95% CI 1.00 to 1.04) and total resection (Hazard Ratio 0.52, 95% CI 0.33 to 0.82) as significant predictors of OS. Increased number of radiation fractions (Hazard Ratio 0.90, 95% CI 0.82 to 0.98), depressive disorder history (Hazard Ratio 0.59, 95% CI 0.37 to 0.95), and total resection (Hazard Ratio 0.52, 95% CI 0.31 to 0.88) were associated with decreased incidence of progression. Notably, patients with depressive disorder history were observed to have more neuro-oncology physician office visits over time (median 12 vs 16 visits, p=0.0121). Patients older than 60 years and those with Medicare (versus private) insurance were less likely to receive as many radiation fractions (p=0.0014) or receive temozolomide concurrently with radiation (Odds Ratio 0.46, p=0.0139). Conclusion: Older glioblastoma patients were less likely to receive as diverse of a treatment regimen as their younger counterparts, which may be partially driven by insurance type. Patients with depressive disorder history exhibited reduced incidence of progression, which may be due to more frequent health care contact during neuro-oncology physician office visits.